The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1159/000512065
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Urethral Stricture Recurrence after Dorsal Onlay Augmented, Buccal Mucosal Graft Urethroplasty

Abstract: <b><i>Introduction:</i></b> This study was carried out to identify the predictors of urethral stricture recurrence after dorsal onlay buccal mucosal graft (BMG) urethroplasty. <b><i>Materials and Methods:</i></b> The medical records of patients with anterior urethral stricture who underwent dorsal onlay BMG urethroplasty at a single tertiary medical center during the period from March 2010 to January 2018 were reviewed. Only patients with ≥2-year follow-up were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
(68 reference statements)
1
9
1
4
Order By: Relevance
“…As our study cohort is rather small, however, and as there were solely 3 patients (6.8%) who had received a prior urethral dilation, we certainly refrain from drawing any definitive conclusions. The risk factors most commonly described by previous series (age, stricture length, body mass index [24][25][26]) were not found to be statistically significant in our analysis.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…As our study cohort is rather small, however, and as there were solely 3 patients (6.8%) who had received a prior urethral dilation, we certainly refrain from drawing any definitive conclusions. The risk factors most commonly described by previous series (age, stricture length, body mass index [24][25][26]) were not found to be statistically significant in our analysis.…”
Section: Discussioncontrasting
confidence: 73%
“…With regard to risk factors for stricture recurrence, the only statistically significant association we found was that patients who had received a prior urethral dilation, when compared to patients with no previous surgery or previous VIU, were less likely to develop a stricture recurrence (p = 0.018). As this association has not yet been reported by previous series [1,[12][13][14][15][24][25][26], we have to assume it is a statistically significant effect without clinical relevance. As our study cohort is rather small, however, and as there were solely 3 patients (6.8%) who had received a prior urethral dilation, we certainly refrain from drawing any definitive conclusions.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have identified inflammatory strictures as a risk factors for urethroplasty failure; specifically, the presence of lichen sclerosus portends a poorer prognosis overall, and has been clearly identified as an independent predictor of stricture recurrence. 8,9 While the exact mechanism remains unclear, it is thought that chronic localized inflammation leads to alterations…”
Section: Discussionmentioning
confidence: 99%
“…The buccal mucosal grafting is advantageous over VWG due to the narrowing of the vagina, but VWG has the advantage in case of patients having unhygienic conditions, smoking, and some oral infections. In the case of VWG, local anesthesia was given to the patients, but in some cases, general anesthesia also needed to be utilized [21][22] .…”
Section: Discussionmentioning
confidence: 99%